2020
DOI: 10.1097/dss.0000000000002614
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Versus Supraperiosteal Injections of Poly-L-Lactic Acid: A Clinical and Imaging Study

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Despite the proximity to the dermis, no alterations in that layer, regarding inflammation, neocolagenesis or elastogenesis, were found in any specimen. The fact the inflammatory reaction and neocollagenesis were only presented around the particles, with no tissue reaction occurring at a distance, confirms the importance of ensuring the products are injected as evenly as possible 29 and at higher dilutions to facilitate the spread of the particles beyond the injection site.…”
Section: Described Excisingmentioning
confidence: 82%
See 1 more Smart Citation
“…Despite the proximity to the dermis, no alterations in that layer, regarding inflammation, neocolagenesis or elastogenesis, were found in any specimen. The fact the inflammatory reaction and neocollagenesis were only presented around the particles, with no tissue reaction occurring at a distance, confirms the importance of ensuring the products are injected as evenly as possible 29 and at higher dilutions to facilitate the spread of the particles beyond the injection site.…”
Section: Described Excisingmentioning
confidence: 82%
“…As some studies have demonstrated, PLLA and CaHA should be injected into the superficial subcutaneous layer, 4,9,29,30 as close as possible to the dermis, because this layer contains the largest amount of fibroblasts and inflammatory cells necessary for neocollagenesis, the final consequence of PLLA and CaHA biostimulation. Consequently, the superficial subcutaneous layer was chosen for the injections in this study as can be seen in Figure 8.…”
Section: Described Excisingmentioning
confidence: 99%
“…However, high-frequency ultrasound was only used in 1 clinical trial to detect side effects associated with PLLA injection; the follow-up time was 5 months, which was far from enough. 10 Our study utilized a high-frequency ultrasound for detection, and the follow-up time was 30 months. The results of our study demonstrated that injectable PLLA was a relatively safe filler because it degraded totally, and no papules and nodules occurred in 80% of subjects after a 30-month injection.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, multiple noninvasive imaging techniques, such as ultrasound, magnetic resonance imaging, and Vectra 3D imaging, have been valuable for effect evaluation and complication diagnosis of facial filling. [9][10][11][12] High-frequency ultrasound with a probe with a frequency of more than 10 MHz can illustrate more significant details of cutaneous structures in different layers and characters of lesions. Herein, it is proposed that high-frequency ultrasound can be utilized as a quick, convenient, and precise method to assess the long-term safety of PLLA injection in nasolabial folds.…”
mentioning
confidence: 99%
“…This type of placement supports maxillary protrusion, lifts the lip, and provides support to the infraorbital tissues, camouflaging volume loss in this area. Importantly, PLLA should be placed as a thin layer, as injection of large boluses can lead to formation of nodules 49 …”
Section: Discussion Of Patient Typesmentioning
confidence: 99%